Blood cholesterol and its related factors among Indonesian blood donors - Nian Afrian Nuari; Efa Nur Aini; Dhina Widayati (International Journal of Public Health Science (IJPHS), 2023)
Blood donation nowadays were considered to improve health status of the donors by declining human’s cholesterol level. The high level of cholesterol inside the blood bags influenced the blood quality. However, there was limited data about cholesterol level and its influencing factor on the blood donors. This cross-sectional study aimed to analyse the associated factors of cholesterol levels in blood donors. This study involved 120 respondents using the purposive sampling as sampling method. Data was collected using questionnaires and blood cholesterol examination. The obtained data was analysed using univariate and bivariate statistic tests with significance level α=0.05. This study found that the majority of respondents aged 35-45 years (60.8%) and male (60.8%). More than half respondents were routine to donate their blood. Although they consumed cholesterol foods, their cholesterol level remained normal (88.3%). This study also found that blood donation had an association with cholesterol level p=0.000, while the other variables did not show any relationship. The normal cholesterol level among blood donors was influenced by frequent blood donation. Further study needs to be explored about the activities and the foods type to identify the cholesterol level among blood donors.